THE EFFECT OF TUMPEK WARIGA-BASED PROJECT-BASED LEARNING ON ELEMENTARY SCHOOL STUDENTS’ CRITICAL THINKING AND COLLABORATION SKILLS IN INTEGRATED SCIENCE AND SOCIAL STUDIES LEARNING - Ni Gusti Ayu Putu Eka Sri Wahyuni; Marungkil Pasaribu; Paulus Abram Hengky; Kasmudin Mustapa; Mery Napitupulu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effect of the Tumpek Wariga-based Project-Based Learning (PjBL) model on students’ critical thinking and collaboration skills in science and social studies (IPAS) learning at SD Negeri Sumbersari. The study employed a quasi-experimental method using two research designs: a Pretest–Posttest Control Group Design for the critical thinking skills variable and a Static Group Comparison Design for the collaboration skills variable. The participants consisted of 17 students in the experimental group and 16 students in the control group. Critical thinking data were collected through a six-item essay test, while collaboration skills data were obtained through structured observations consisting of 12 indicators across five aspects. Data were analyzed using normality and homogeneity tests, paired samples t-test, Mann–Whitney U test, independent samples t-test, N-Gain analysis, and Cohen’s d effect size. The results revealed that the Tumpek Wariga-based PjBL model had a positive effect on students’ critical thinking skills, as indicated by an N-Gain score of 0.35 (moderate category) and an effect size of 0.38 (small category). The model also demonstrated a highly significant effect on collaboration skills, with the experimental group achieving an average score of 83.58% (very high category), significantly higher than that of the control group (51.56%), and an effect size of 5.402 (very large category). These findings suggest that the integration of local wisdom through the Tumpek Wariga-based PjBL model is effective in fostering elementary school students’ critical thinking and collaboration skills.